Sobre uma mulher quebrada: dança como memória de um improviso feminino - JESUS, Nayara Silva de (2021)
The research seeks to understand the relationships between dance and memory, if using a photographic experiment, which focuses on the female body as a trigger for imaging. The methodology used corresponds to the qualitative studies according to Marconi and Lakatos (2007) of researches in arts starting from the conception of the work “in process”, “being made”, instead of analyzing it under the finished work bias, according to Cecilia Salles (2007). In this sense, improvisation dance emerges as the elo-element of encounter between body-dance-memory of a female being that crosses several aspects in its social context and is crossed within it by other feminine contexts. As remembrance of a female improvisation comprises the minutiae of the process of creation from a space of dialogues with women, who dance, each with its interpessualities of memories, affections and perceptions (Merleau- Ponty, 1999) of the female body that moving in the contemporary world.